Tissue culture based clean planting material: A niche and profitable venture - Theivanai, M; Awasthi, O P; Shukoor, Amina; Rai, Aanamika (Indian Horticulture, 2024)
The availability of quality and true-to-type planting material is prerequisite for any orchard establishment. In this context, the Government’s initiative on establishment of "Atmanirbhar Clean Plant Program" in high value horticultural crops, particularly fruit crops are boon to the orchardist. In vegetatively propagated perennial fruit crops, it is relatively difficult to obtain disease-free quality planting materials through conventional propagation methods, which however, can be achieved through the tissue culture techniques retaining the benefit of vegetative propagation and reduced juvenility. In vitro culture techniques are indispensable for the production of uniform, season independent, disease-free and genuine planting material in less time and space. The innovative cost-effective tissue culture technique like bioreactors and bio-immune can enhance the production of immune planting materials of high quality. In near future, production of tissue culture based clean planting material has the potential not only to alter social organization of nursery industry but can also be a proficient occupation for women and young entrepreneurs.